2010
DOI: 10.1159/000288289
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Prognosis of Childhood Atopic Dermatitis: A Multicenter Study in Turkey

Abstract: Background:Childhood atopic dermatitis (AD) is classically accepted as initial finding of atopic march; however, nonatopic cases do not follow this course. The aim of this study was to determine the characteristics and prognosis of AD in childhood in Turkey. Methods:The study included 531 children with AD that presented to pediatric allergy departments in 11 different regions of Turkey. Age at diagnosis, total serum and inhalant-specific immunoglobulin E (IgE) levels and allergen skin prick test results were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
1
5
0
3
Order By: Relevance
“…Studies performed found a strong relation between eczema and familial atopy (20). In a study including 531 children with AD performed in our country, the rate of familial atopy was reported to be 56.5% (21). In our study, familial atopy was found in approximately half of our subjects (53.5%).…”
Section: Discussionsupporting
confidence: 55%
“…Studies performed found a strong relation between eczema and familial atopy (20). In a study including 531 children with AD performed in our country, the rate of familial atopy was reported to be 56.5% (21). In our study, familial atopy was found in approximately half of our subjects (53.5%).…”
Section: Discussionsupporting
confidence: 55%
“…AD'de pozitif aile öyküsünün majör risk faktörlerinden birisi olarak kabul edilmesi genetik faktörlerin önemini vurgular (7). Ülkemizde yapılan çok merkezli çalışmanın sonucunda da AD'li hastalarda ailede allerji öyküsü %56.5 olarak bildirilmiştir (8). Çalışmamızda da AD'li çocukların %40.7'sinde ailede allerji öyküsü saptanmıştır.…”
Section: Discussionunclassified
“…in a certain order, beginning with the onset of atopic dermatitis, food allergies, then asthma and allergic rhinitis. [86][87][88] According to the most recent Global Burden of Disease report (GBD, 1990-2019), 34.3 million Indians are estimated to suffer from asthma, which represents around 13% of the global burden. 89 Recent studies have also noted a possible increase in the prevalence of allergic rhinitis and asthma, however eczema remains uncommon in the Indian population compared to other global regions.…”
Section: Food Allergy Ris K Fac Tor S and Their Lik Ely Influen Ce On...mentioning
confidence: 99%